KEPADATAN POPULASI APHID Aphis gossypii (Glover) (Hemiptera: Aphididae) PADA TANAMAN KENTANG DI KAMPUNG BATU KECAMATAN DANAU KEMBAR KABUPATEN SOLOK - Witra, Ana; Jasmi, Jasmi; Pratiwi, Putri (STKIP PGRI Sumbar, 2014)
ABSTRACT The population of aphids (Aphis gossypii) in Kampung Batu Kembar lake district of Solok decrease the production of vegetables. One of the vegetables that there are in the areas of this Batu village is potatoes. The purpose of this study was to determine the population density of Aphis gossypii on potato in Kampung Batu Kembar Lake District of Solok. This study was conducted in September-November 2013 with a descriptive survey method by direct collection against A. gossypii existing research in the location. Field sampling conducted on potato tubers and grow new potatoes will be harvested a month. Physical environmental factors measured are temperature, pH and soil moisture. Widely used as a study area of about 30 x 20 m. The characteristics of A. gossypii were found on potato in Kampung Batu subdistrict Kembar Lake are body size from 1.1 to 3 mm , konikel one pair , there are winged and wingless and there are a variety of body colors such as black, green, and yellow. From the research that has been conducted on potato in Kampung Batu Kembar Lake District of Solok was concluded on potato tubers grown induvidu obtained 7.69 / month clumps and the potatoes will be harvested obtained 4.6 induvidu / clump. Population density of A. gossypii were found already passed the threshold of pest control.